Identifying residents' educational needs to optimising postgraduate medical education about shared decision-making. Issue 10 (October 2022) - Baghus, Anouk; Giroldi, Esther; Timmerman, Angelique; Schmitz, Emmeline; Erkan, Fatma; Röhlinger, Darwin; Pieterse, Arwen; Dielissen, Patrick; Kramer, Anneke; Rietmeijer, Chris; Muris, Jean; van der Weijden, Trudy
Abstract: Objective: To investigate how to optimise resident engagement during workplace learning of shared decision-making (SDM) by understanding their educational needs. Methods: A qualitative multicentre study was conducted using video-stimulated interviews with 17 residents in General Practice. Video recordings of residents' recent clinical encounters were used to facilitate reflection on their educational needs. Results: Data analysis resulted in five themes regarding residents' educational needs for learning SDM: acquiring knowledge and skills needed to perform SDM; practising SDM; reflection and feedback; longitudinal and integrated training; and awareness and motivation for performing SDM. Conclusion: Residents expressed a need for continuous attention to be paid to SDM during postgraduate medical education. That would help them engage in two parallel learning processes: acquiring the knowledge and skills necessary to perform SDM, and practising SDM in the clinical workplace. Alignment between the educational curriculum, workplace learning and resident learning activities is essential to operationalise SDM attitude, knowledge and skills into clinical performance. Practice Implications: The identified educational needs provide ingredients for fostering the development of SDM proficiency. The findings suggest that residents and clinical supervisors need parallel training to bridge the gap between education and clinical practice when learning SDM. Highlights: Awareness, knowledge and skills are required to translate SDM into clinical performance. Engagement in learning is prerequisite for continued application of SDM in clinical encounters. Observation, evaluation and reflection on clinical performance support learning. Learning SDM requires a longitudinal curriculum with increasing clinical complexity. Clinical supervisors are important role models for tailoring SDM during workplace learning.